2017
DOI: 10.1246/cl.170168
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Giant Polyion Complex Vesicles (G-PICsomes) with Polyphosphobetaine Shells Composed of Oppositely Charged Diblock Copolymers

Abstract: Diblock copolymers composed of a water-soluble polyphosphobetaine block with a short chain length and either a cationic or anionic block were prepared. Giant polyion complex vesicles (G-PICsomes), with a size on the order of micrometers, were prepared by dialysis from a mixture of oppositely charged diblock copolymers in a 1.5 M NaCl aqueous solution against pure water. Hydrophilic guest molecules could be encapsulated into the G-PICsomes. Vesicles formed from phospholipids, 1 low-molecularweight surfactants, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…PIC micelles can encapsulate charged compounds such as metal ions, proteins, and nucleic acid in the PIC core via electrostatic interactions [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Recently, water-soluble PIC micelles were prepared with hydrophilic poly(2-methacryloyloxyethyl phosphorylcholine) (PMPC) coronas without net charge [ 12 , 13 , 14 ]. PMPC has pendant phosphorylcholine groups with the same chemical structure as the hydrophilic part of phospholipids comprising cell membranes.…”
Section: Introductionmentioning
confidence: 99%
“…PIC micelles can encapsulate charged compounds such as metal ions, proteins, and nucleic acid in the PIC core via electrostatic interactions [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Recently, water-soluble PIC micelles were prepared with hydrophilic poly(2-methacryloyloxyethyl phosphorylcholine) (PMPC) coronas without net charge [ 12 , 13 , 14 ]. PMPC has pendant phosphorylcholine groups with the same chemical structure as the hydrophilic part of phospholipids comprising cell membranes.…”
Section: Introductionmentioning
confidence: 99%
“…This indicated that [NaCl] strongly influenced the T p value of the PSBP/CTAB complex. At an [NaCl] of 0.06 M, the T p of the PSBP/CTAB complex was 31.2 °C, whereas it decreased to 4.8 °C for an [NaCl] of 0.15 M. This might be due to the counterions, Na + and Cl − , replacing the anionic and cationic groups in PSBP and CTAB [ 60 ], which would partially reduce the total energy required to break the electrostatic interactions that form the complex.…”
Section: Resultsmentioning
confidence: 99%
“…Artificial membranes can be produced also solely by synthetic polymers based on the self-assembly of block copolymers. Yusa et al have extensively studied the supramolecular assembly of block copolymers in an aqueous solution mediated by the formation of polyion complex [17][18][19]. The formation of polyion complex originated in the multi-point electrostatic interactions between polymer chains aids the self-assembly in water that plays a similar role to Figure 2 Chemical structures of polymers for the spontaneous formation of nanodiscs (1) [14] and supramolecular assembly via polyion complex formation (2) [19].…”
Section: Supramolecular Artificial Biomembranes Formed By Synthetic M...mentioning
confidence: 99%
“…In contrast, the block polymer with a zwitterionic domain shorter than the charged domain assembles into vesicles [ 18 ]. Giant polyion complex vesicles in μm scale were also produced by the dialysis of the polymer solution containing a high concentration of sodium chloride as a salt due to the gradual modulation of the electrostatic interaction between charged domains [ 19 ].…”
Section: Supramolecular Artificial Biomembranes Formed By Synthetic M...mentioning
confidence: 99%